2017
DOI: 10.4049/jimmunol.1602102
|View full text |Cite
|
Sign up to set email alerts
|

A20 Restrains Thymic Regulatory T Cell Development

Abstract: Maintaining immune tolerance requires the production of Foxp3-expressing regulatory T (Treg) cells in the thymus. Activation of NF-κB transcription factors is critically required for Treg cell development, partly via initiating Foxp3 expression. NF-κB activation is controlled by a negative feedback regulation through the ubiquitin editing enzyme A20, which reduces proinflammatory signaling in myeloid cells and B cells. In naive CD4+ T cells, A20 prevents kinase RIPK3-dependent necroptosis. Using mice deficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 55 publications
0
21
0
Order By: Relevance
“…Differences in T-cell-specific Tnfaip3 deletion between the two mouse strains could indicate that either CD8 + T-cells drive inflammation in Tnfaip3 maT-KO mice or CD4 + T-cells have increased regulatory function in Tnfaip3 CD4-KO mice. Indeed, regulatory T cell (Treg) proportions were increased in Tnfaip3 CD4-KO mice, because of a reduced IL-2 dependence for their development ( 93 ). In vitro activated CD4 + T-cells from Tnfaip3 CD4-KO mice died quicker than wild-type T-cells ( 14 , 15 ), due to A20/TNFAIP3’s control on necroptosis ( 14 ) and autophagy ( 15 ).…”
Section: Immune Cell-specific Deletion Of A20/ Tnfaip3 mentioning
confidence: 99%
“…Differences in T-cell-specific Tnfaip3 deletion between the two mouse strains could indicate that either CD8 + T-cells drive inflammation in Tnfaip3 maT-KO mice or CD4 + T-cells have increased regulatory function in Tnfaip3 CD4-KO mice. Indeed, regulatory T cell (Treg) proportions were increased in Tnfaip3 CD4-KO mice, because of a reduced IL-2 dependence for their development ( 93 ). In vitro activated CD4 + T-cells from Tnfaip3 CD4-KO mice died quicker than wild-type T-cells ( 14 , 15 ), due to A20/TNFAIP3’s control on necroptosis ( 14 ) and autophagy ( 15 ).…”
Section: Immune Cell-specific Deletion Of A20/ Tnfaip3 mentioning
confidence: 99%
“…The Treg frequency is enhanced although Tregs are less functional than the wild-type counterparts ( 44 ). Recently, it was demonstrated that another negative regulator of NF-κB—ubiquitin-editing enzyme A20—restricts nTreg development; however, A20-/- Tregs are completely functional in vivo ( 45 ). Interestingly, while A20 terminates NF-κB signaling, CYLD prevents spontaneous NF-κB activation.…”
Section: The Nf-κb Team In Treg Biologymentioning
confidence: 99%
“…Consistent with this, A20-deficient mice are hypersensitive to TNF exposure and die perinatally because of severe inflammation and multiorgan failure [42]. Intriguingly, A20 is recently shown to regulate the de novo generation of tTreg in a cell-intrinsic manner, while the suppressor function of A20-deficient Treg is unchanged in vitro [43].…”
Section: Tnf/tnfr Signaling Pathwaysmentioning
confidence: 74%